Epileptic Encephalopathy, Myoclonus–Dystonia, and Premature Pubarche in Siblings with a Novel C-Terminal Truncating Mutation in ATRX Gene - Giacomini, Thea; Vari, Maria Stella; Janis, Sara; Prato, Giulia; Pisciotta, Livia; Rocchi, Alessia; Michelucci, Angela; Di Rocco, Maja; Gandullia, Paolo; Mattioli, Girolamo; Sacco, Oliviero; Morana, Giovanni; Mancardi, Maria Margherita (Neuropediatrics, 2019)
The X-linked alpha thalassemia mental retardation (ATR-X) syndrome is a genetic disorder caused by X-linked recessive mutations in ATRX gene, related to a wide spectrum of clinical manifestations, such as alpha thalassemia, developmental delay, genital abnormalities, and gastrointestinal disorders. Patients with ATR-X syndrome can suffer from different types of epileptic seizures, but a severe epileptic encephalopathy pattern has not been described to date. We describe, for the first time, two brothers with genetically confirmed ATR-X syndrome who presented with drug-resistant epileptic encephalopathy, with tonic and polimorphic seizures reported in the elder brother and epileptic spasms in the younger brother. Moreover, both brothers showed a peculiar movement disorder with myoclonus–dystonia, worsened during periods of distress or pain. These cases expand the clinical spectrum of ATR-X syndrome and open new opportunities for the molecular diagnosis of ATRX mutations in male patients with severe epileptic encephalopathies and movement disorders.
Keywords: ATR-X syndrome; epileptic encephalopathy; myoclonus-dystonia; premature pubarche